Pembelajaran Ekonomi dalam Islam pada Materi Mudharabah di Pondok Pesantren - Muhammad Tri Ramdhani; Lastaria Lastaria; Ariyadi Ariyadi (Anterior Jurnal, 2019)
This process begins with preliminary activities that provide stimulus in advance for students to be proactive in learning that will be implemented and present some problems in life-related to learning material. Then proceed with the core activities beginning with observing such as asking students to read a reference book about mudaraba and also given the opportunity to observe some questions about what happened related to the material discussed and observe the slides that are displayed. Then the questioning process is carried out with the process of students to answer the pre-test given in the form of questions, then provide the opportunity for students to ask questions related to observations made previously about mudaraba and accommodate questions from them and give opportunity to each student or point randomly to answer a question from his friend. After observing and asking questions, it is continued by exploring some of the results carried out previously such as searching for answers to pre-test questions by reading some of the references contained in the teaching book or other book references, then in this activity collecting information from questions and answers conducted and completing it by reading the textbooks and other reference books related to syirkah material and a discussion on the problems obtained. At the core, activity ended with communicating inviting students to make a report on the results of discussions that have been done by presenting in front of the class and given a response from other groups and ending affirmation of the learning outcomes.